The Effect of Fermentor Dosage on Tofu Dregs as Tubifex sp. Culture Media on Population and Biomass - Vernanda Febiola Djatmiko; Sukendi Sukendi; Netti Aryani (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2023)
Natural feed is an initial feed that has a complete nutritional content and is closer to the biological needs of fish larvae, one of which is Tubifex sp. Tubifex sp is a type of natural feed that is very important in freshwater aquaculture activities, especially for catfish hatcheries. Tubifex sp. has a fairly high nutritional content, 57% protein, 13.3% fat, 2.04% crude fiber, 3.6% ash content and 87.7% water. The purpose of this study was to determine the effect of fermentor dosing on tofu dregs as a Tubifex sp. culture medium on population and biomass growth rates. This research was conducted in August - October 2023 located in the laboratory of the Faculty of Fisheries and Marine, Riau University. The research method used was an experimental method using a completely randomized design (CRD), consisting of 4 treatments and 3 replications. The fermentor dose used was in the treatment P0 (0.0 ml), P1 (0.5 ml), P2 (1.0 ml), P3 (1.5 ml). The results of this study indicated that the dose of fermentor on tofu dregs as a culture medium for Tubifex sp. had a significant effect (P<0.05) on population and biomass. The highest population and biomass were found in treatment P2, with a population of 13519 ind and a biomass of 49.52 grams which were reared for 56 days. Based on the results of the study it can be concluded that giving fermenter doses to tofu dregs as a Tubifex sp. culture medium can increase population and biomass.